2013
DOI: 10.1016/j.physletb.2013.10.072
|View full text |Cite
|
Sign up to set email alerts
|

Infrared dynamics in de Sitter space from Schwinger–Dyson equations

Abstract: We study the two-point correlator of an O(N) scalar field with quartic self-coupling in de Sitter space. For light fields in units of the expansion rate, perturbation theory is plagued by large logarithmic terms for superhorizon momenta. We show that a proper treatment of the infinite series of self-energy insertions through the Schwinger-Dyson equations resums these infrared logarithms into power laws. We provide an exact analytical solution of the Schwinger-Dyson equations for infrared momenta when the self-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 58 publications
(113 reference statements)
12
86
0
Order By: Relevance
“…For example, recently, it has been shown that the stochastic and the in-in Lorentzian calculations are equivalent at the level of Feynman rules for massive fields, when computing equal-time correlation functions in the leading IR approximation [21], in agreement with previous arguments [22]. The evaluation of the field variance in the large N limit gives the same result in the three approaches, up to next to leading order (NLO) in 1/N , in the IR limit [15,16]. The connection between the Feynman diagrams for computing correlation functions in the in-in formalism and the analytically continued ones obtained in the Euclidean space has been described in detail in [23,24] for massive fields.…”
Section: Jhep09(2016)117supporting
confidence: 75%
See 4 more Smart Citations
“…For example, recently, it has been shown that the stochastic and the in-in Lorentzian calculations are equivalent at the level of Feynman rules for massive fields, when computing equal-time correlation functions in the leading IR approximation [21], in agreement with previous arguments [22]. The evaluation of the field variance in the large N limit gives the same result in the three approaches, up to next to leading order (NLO) in 1/N , in the IR limit [15,16]. The connection between the Feynman diagrams for computing correlation functions in the in-in formalism and the analytically continued ones obtained in the Euclidean space has been described in detail in [23,24] for massive fields.…”
Section: Jhep09(2016)117supporting
confidence: 75%
“…We will also show that the corrections of order 1/N of our result coincide in the leading IR approximation with the ones of refs. [15,16], which are the most precise results known so far for this model and were obtained working in the leading IR approximation and directly in the framework of the QFT in Lorentzian spacetime. Our results improve on those by including systematically the corrections coming from the interactions of both IR and UV sectors.…”
Section: Jhep09(2016)117mentioning
confidence: 82%
See 3 more Smart Citations